Scalloped tongue: an additional, accessible and useful tool to detect severe obstructive sleep apnea? - Guimarães, Francisca Nieto; Canadas, Joana; Cunha, Maria Gonçalves; Durão, Vera; Rosa, Paula; Rabahi, Marcelo; Zou, Ding; Magalhães da Silveira, Flávio (Frontiers in Sleep, 2025)
The anatomy of the upper airway can influence the risk of obstructive sleep apnea (OSA). However, there is limited evidence supporting the link between scalloped tongue (ST) and nocturnal intermittent hypoxia. This study aimed to investigate if ST could serve as a clinical indicator of OSA, particularly severe OSA. Over a 4-month period from October 2023 to January 2024, 160 patients underwent level 1 polysomnography at a sleep laboratory in Brazil. Demographics, body mass index (BMI), neck circumference (NC), presence of ST, Epworth Sleepiness Scale score, apnea hypopnea index, oxygen desaturation index (ODI) and time under 90% of oxygen saturation were included in a database. Logistic and multiple linear regression models were performed. A p-value <0.05 was considered as the lower threshold of significance. Most (90%) patients had OSA, 41% classified as severe. Older age and a wider NC significantly increased the risk of OSA. Older age, higher BMI, wider NC, and ST significantly increased the risk of severe OSA, and there was a statistically significant positive correlation between the presence of ST and ODI (p = 0.001). The presence of ST increased ODI by 6.723/h, adjusted for age, BMI, and NC. The combined presence of NC ≥ 40 cm and ST significantly increased the risk of severe OSA (OR 4.210, p < 0.001), and significantly impacted ODI estimates. Incorporating tongue and NC assessment in OSA screening, both objective and easily observable clinical signs, may help physicians in the prompt identification of severe cases that benefit from early positive airway pressure therapy.